Gladiators and ancient Rome - Ganeri, Anita, 1961- (Milwaukee, Wis. : G. Stevens, 2005)
Describes life in ancient Rome as well as the gladiators who fought for the entertainment of it populace.
First published: Great Britain : ticktock Media, 2005.
3.2
K-3
Keywords: Gladiators -- Juvenile literature; Gladiators; Gladiators; Rome -- Social life and customs -- Juvenile literature; Rome -- Social life and customs; Rome -- Social life and customs